Primary Aldosteronism: A Practical Approach to Diagnosis and Treatment - Thakkar, Roopal B. (J Clin Hypertens (Greenwich), 2007)
Primary aldosteronism (PA) may account for as many as 10%–14% of hypertension cases. The plasma aldosterone concentration/plasma renin activity ratio is a simple screening test for PA that should be performed in all patients with refractory/severe hypertension, spontaneous or provoked (by diuretics) hypokalemia, or a requirement for excessive potassium supplementation to maintain normokalemia. PA can be confirmed by a fludrocortisone suppression test or 24‐hour urine collection for aldosterone. Confirmatory testing should be followed by high‐resolution computerized tomography of the adrenal glands to distinguish bilateral hyperplasia or an adenoma. A solitary tumor greater than 1 cm in size in a younger patient is an indication for surgery; all other (nondiagnostic) findings should be followed by bilateral adrenal venous sampling (if available) to identify a unilateral cause of PA. Treatment for a later alizing positive study is surgical; spironolactone or another mineralocorticoid receptor antagonist is the treatment of choice for a nonlateralizing study. If adrenal venous sampling is not readily available, patients may be successfully treated pharmacologically.